ISLAMIC EDUCATION IN INDONESIA AND MALAYSIA: THE EXISTENCE AND IMPLEMENTATION UNTIL 20th CENTURY - Saiful Akhyar Lubis (Badan Litbang dan Diklat Kementerian Agama RI, 2017)
AbstractThis study discusses the comparison between the existence and the implementation of Islamic Education in Indonesia and Malaysia both fromreligious educational institutions and public educational institutions. The main problem focuses on: what are the issues that covered equality and diï¬€erences based on the existence and implementation, and also what matters are dominantly and substantially considered as supporting factors for the cause of those two points (existence and implementation). Methodologically, this study uses library research with qualitativeÂ approach as sources in writing. The study describes the policy from the two countries toward Islamic Education including their goals and objectives. In addition, this study is also exploring the development of Islamic Education in the two countries based on the historical facts and current situation. The result of this study indicates that Islamic education plays an important role in developing both nations, and as such, it is granted a special position in the national educational laws of both of these states.AbstrakStudi ini membahas perbandingan antara keberadaan dan implementasi Pendidikan Islam di Indonesia dan Malaysia baik dari lembaga pendidikan agama maupun lembaga pendidikan umum. Masalah utamanya berfokus pada: isu apasaja yang mencakup persamaan dan perbedaan berdasarkan keberadaan dan implementasi, dan juga hal-hal yang secara dominan dan secara substansial dianggap sebagai faktor penunjang penyebab dua poin tersebut (keberadaan dan implementasi). Secara metodologis, studi ini menggunakan penelitian kepustakaan dengan pendekatan kualitatif sebagai sumber dalam penulisan. Penelitian ini menggambarkan kebijakan dari kedua negara terhadap Pendidikan Islam termasuk tujuan dan sasaran mereka. Selain itu, penelitian ini juga mengeksplorasi perkembangan Pendidikan Islam di kedua negara berdasarkan fakta sejarah dan situasi saat ini. Hasil penelitian ini menunjukkan bahwa pendidikan Islam memegang peran penting dalam mengembangkan kedua negara, dan karena itu diberikan posisi khusus dalam undangundang pendidikan nasional di kedua negara ini.